Effect Of Administration Of Binahong Leaf Ethanol Extract On Reducing Blood Sugar Levels In Type 2 Diabetes Mellitus Model Rat - Rusdiana, Rusdiana; Rina Amelia; Cut Putri Hazlianda (TALENTA Publisher, Universitas Sumatera Utara, 2025)
ABSTRACT Background. Type 2 diabetes mellitus (T2DM) is characterized by elevated levels of blood glucose. Binahong leaves contain various metabolites such as flavonoids which are known to have antidiabetic effects. The research aims to determine the effect of administering ethanol extract of Anredera cordifolia (Ten.) Steenis leaves on reducing blood sugar levels in T2DM rats. Methods. This study is a true experimental in vivo with a pre-post test control group design. This study used 30 rats consisting of 6 groups: normal control, negative control, positive control (metformin), ethanol extract of binahong leaves dose 25 mg/kgBW, ethanol extract of binahong leaves dose 50 mg/kgBW, and ethanol extract of binahong leaves dose 100 mg/kgBW. The treatment group was induced by HFD for 14 days and injected with streptozotocin 30 mg/kgBW followed by ethanol extract of binahong leaves for 14 days. Rat blood sugar levels were evaluated 7 and 14 days after administration of binahong leaf ethanol extract. Data analysis used parametric and Wilcoxon non-parametric statistical tests. Results. Ethanol extract of binahong leaves doses of 25 mg/kgBB, 50 mg/kgBW, and 100 mg/kgBB affected reduced blood glucose significantly. Conclusion. Ethanol extract from binahong leaves can reduce the blood glucose in T2DM rats significantly. Keyword: Diabetes Mellitus, Hyperglycemia, Binahong Leaf Extract, Flavonoid, Streptozotocin